2020
DOI: 10.35848/1882-0786/abb871
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of laser-irradiated ultrananocrystalline diamond/amorphous carbon composite films prepared by coaxial arc plasma

Abstract: Ultrananocrystalline diamond/hydrogenated amorphous carbon films were synthesized by coaxial arc plasma deposition. The morphological and structural evolutions of the films driven by laser irradiation (ArF, 193 nm, 20 ns) are examined at different laser energies (0.4–1 J cm−2). Up on laser irradiation, the films revealed hydrogen effusions accompanied by the transformation of sp3 into sp2-hybridization carbon. However, the film irradiated at 0.8 J cm−2 exhibited higher sp3 fractions, which can be attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Similar results have been reported in laser-irradiated nanocrystalline diamond and low-energy ion-irradiated diamond. [41,42] The amorphous carbon of the intermediate layer formed at the interface should partially originate from the damage of FIB during TEM sample fabrication processes. It has been reported that the structural and compositional properties of interfaces fabricated by SAB were largely modified during FIB processes operated at room temperature, especially for wide bandgap materials.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been reported in laser-irradiated nanocrystalline diamond and low-energy ion-irradiated diamond. [41,42] The amorphous carbon of the intermediate layer formed at the interface should partially originate from the damage of FIB during TEM sample fabrication processes. It has been reported that the structural and compositional properties of interfaces fabricated by SAB were largely modified during FIB processes operated at room temperature, especially for wide bandgap materials.…”
Section: Resultsmentioning
confidence: 99%
“…The pulse duration of the laser pulse plays a critical role in determining the crystallinity . The regrowth velocity is low for broader pulses, which provides the interfacial atoms of the melt front sufficient time to ascend the lattice positions and leads to the crystallization . This framework provides a guideline to standardize the PLA parameters for controlling the undercooling and thereby the regrowth velocity, which ultimately enables to fabricate structures with desirable properties.…”
Section: Resultsmentioning
confidence: 99%
“…39 The regrowth velocity is low for broader pulses, which provides the interfacial atoms of the melt front sufficient time to ascend the lattice positions and leads to the crystallization. 40 This framework provides a guideline to standardize the PLA parameters for controlling the undercooling and thereby the regrowth velocity, which ultimately enables to fabricate structures with desirable properties. As this is a liquid-phase-mediated ultrafast crystal growth process, dopants do not segregate or form clusters, rather the solute trapping phenomenon is used to effectively dope the material at the high concentration level.…”
Section: Electrical Transport Measurementsmentioning
confidence: 99%
“…Compared to the undoped film (only in H 2 atmosphere), all nitrogen-doped NCD films (3, 5, 6, 8 at.%) exhibited three additional components, as shown in Figure 5 a. For more analysis of peak components, NEXAFS spectra of minimum (3 at.%) and maximum (8 at.%) values of nitrogen contents were deconvoluted into component peaks, with the similar processes described in our previous work [ 29 ], as presented in Figure 5 b. In Figure 5 b, the NEXAFS spectra with peak positions at 286.7 and 289.2 eV originated from π *C=N and σ *C−N [ 30 ].…”
Section: Resultsmentioning
confidence: 86%